The effect of increased shooting distance on energy flow in basketball jump shot - Nakano, N.; Fukashiro, S.; Yoshioka, S. (Sports Biomechanics, 2020)
The aim of this study is to clarify the effect of shooting distance on energy flow in basketball jump shot. Ten male right-handed basketball players participated in this study, and three successful shots at three different distances (short condition, equating to a free-throw; long condition, equating to a three-point shot; and mid condition, equating to the mid-point of the short- and long-condition shots) were recorded using a motion capture system and force platforms. Kinetic variables of joints during shooting were analysed using inverse dynamics method. Our results showed that the joint work was not significantly different for short- and mid-condition shots; however, the amount of energy transferred from the torso to the shooting arm by the shoulder joint force increased significantly for the mid-condition shots ([Formula: see text] as opposed to [Formula: see text] J/kg, [Formula: see text]), whereas between the mid- and long-conditions, it was found that the joint work in the lower limbs increased significantly ([Formula: see text] as opposed to [Formula: see text] J/kg, [Formula: see text]). These results suggest that sufficient energy transfer from the lower limbs to the shoot arms is important to keep the motions of the shooting arms approximately constant when shooting from various distances.